Perlindungan Hukum Terhadap Anak Korban Pelecehan Seksual Yang Diselesaikan Secara Adat Perspektif Viktimologi Di Kabupaten Simeulue - Umra, Mulia Sri; Salam , Abdul Jalil; Amrullah, Amrullah (Journal of Innovative and Creativity, 2026)
The study purpose was to analyze the legal protection of child victims of sexual harassment resolved through customary mechanisms in Simeulue District, viewed from victimology and Islamic criminal law perspectives. This issue arises because customary dispute resolution is often prioritized within the community, yet it may not fully guarantee the rights and recovery of child victims. Therefore, this study seeks to examine how legal protection is implemented, identify its weaknesses, and evaluate it through relevant theoretical frameworks. Materials and methods. This research employed an empirical juridical approach using case, statutory, and conceptual approaches. Data were collected through field research, including interviews and documentation, as well as literature review of relevant laws and theories. The data were then analyzed descriptively to provide a comprehensive understanding of the issue. Results. The findings reveal that customary dispute resolution mechanisms in Simeulue emphasize deliberation, reconciliation, and the preservation of family honor. However, these mechanisms often marginalize the victim’s position, limit their participation in the process, and potentially lead to revictimization. From a victimology perspective, such practices fail to ensure adequate protection, recovery, and justice for victims. Furthermore, Islamic criminal law classifies sexual harassment as a jarīmah ta‘zīr, which requires firm sanctions to uphold human dignity, provide deterrence, and ensure justice for victims and society. Conclusions. It can be concluded that although customary mechanisms play an important role in local dispute resolution, they are insufficient in providing comprehensive legal protection for child victims of sexual harassment. Therefore, it is necessary to strengthen the integration between customary practices and formal legal systems, ensuring that victims’ rights, protection, and justice are fully guaranteed.